Knowledge of primary health care professionals on health policies for the riverside population - Leandro Barreto da Silva; Ivaneide Leal Ataíde Rodrigues; Laura Maria Vidal Nogueira; Ingrid Fabiane Santos da Silva; Felipe Valino dos Santos
ABSTRACT Objectives: to analyze the knowledge of health professionals on the health policies for the riverside population; identify how health practices with this group are developed; and discuss facilitators and barriers for the implementation of these policies. Methods: qualitative and descriptive study with 24 professionals from the Riverside Family Health Strategy Teams in the city of Belém-Pará. Data were collected in individual interviews and analyzed by Content Analysis. Results: although professionals demonstrate knowledge about public health policies, there is a need to expand and strengthen knowledge about health policies for the riverside population. The activities directed to the communities took place in the Unit itself, and some did not occur due to insufficient material and human resources. Final Considerations: the greatest barrier for the organization of health care is the lack of material and human resources, and the most prominent facilitator was the union and cohesion of the health team.